2022
DOI: 10.3390/ijms23148050
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Binding Determinants for Different Classes of Competitive and Noncompetitive Inhibitors of Glycine Transporters

Abstract: Glycine transporters are interesting therapeutic targets as they play significant roles in glycinergic and glutamatergic systems. The search for new selective inhibitors of particular types of glycine transporters (GlyT-1 and GlyT-2) with beneficial kinetics is hampered by limited knowledge about the spatial structure of these proteins. In this study, a pool of homology models of GlyT-1 and GlyT-2 in different conformational states was constructed using the crystal structures of related transporters from the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Several GlyT inhibitors have been described in the last two decades. Although they selectively inhibit either astrocytic GlyT1 or neuronal GlyT2, animal models of human disorders have also pointed to the need for non-selective GlyT inhibitors [85]. Modeling neuropathic pain in rats has indicated the involvement of both types of GlyTs in the pathological alterations of spinal cord neuronal circuitries [85][86][87][88].…”
Section: Classification Of Glycine Transporter Inhibitorsmentioning
confidence: 99%
“…Several GlyT inhibitors have been described in the last two decades. Although they selectively inhibit either astrocytic GlyT1 or neuronal GlyT2, animal models of human disorders have also pointed to the need for non-selective GlyT inhibitors [85]. Modeling neuropathic pain in rats has indicated the involvement of both types of GlyTs in the pathological alterations of spinal cord neuronal circuitries [85][86][87][88].…”
Section: Classification Of Glycine Transporter Inhibitorsmentioning
confidence: 99%
“…During the transport cycle, three main conformational states of transporters can be distinguished: an outward-open state, allowing for access to the S1 site for the substrate and ions from the extracellular side; an occluded state, where access to the S1 site is blocked from both sides of the membrane; and an inward-open state, allowing for the release of the substrate and ions into the cell [ 10 , 11 ]. Analysis of the available crystal structures of SLC6 proteins and the results of in silico studies revealed that competitive inhibitors bind with a high affinity to the S1 site, blocking the transporter in an outward-open state [ 6 , 7 , 12 , 13 , 14 , 15 , 16 ]. Within the vestibule of the transporter, an allosteric binding site (S2) was identified, in which, as observed for S-citalopram in SERT, additional ligand molecules can bind, thus modulating the affinity of ligands (including itself) that bind in the S1 site [ 8 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%